Rhetoric of affections: advertising, seduction and truth - Barroso, Paulo (2019)
Advertising frequently provokes pathos and elicits emotional reactions (e.g. fear, patriotism, guilt, pity, joy, satisfaction, etc.) to get what it wants. Considering the rhetorical ability and the proliferation of advertisements in the contemporary Western societies, this article analyzes these omnipresent, seductive and affective discourses. Following a theoretical and reflexive approach, the objective is to argue and understand the power of rhetoric developing seduction and provoking affections in advertising strategies.